MyoD is required for the differentiation of Myo/Nog cell progenitors of myofibroblasts in explants of human lens tissue - Gerhart, Jacquelyn; Crispin, Mara; Heist, Brian; Mathers, Keith; Infanti, Joseph; Venuti, David; Richards, Joseph F.; Morency, Steven; Hatcher, Cathy; George-Weinstein, Mindy (Frontiers in Ophthalmology, 2025)
IntroductionPosterior capsule opacification (PCO) is a complication of cataract surgery that impairs vision. Clouding and distortion of the posterior capsule occur as a result of cell migration, deposition of extracellular matrix proteins and contractions of myofibroblasts. The focus of this study is a subpopulation of cells within the lens, called Myo/Nog cells, that differentiate into myofibroblasts in response to wounding. Myo/Nog cells express the skeletal muscle specific transcription factor MyoD, bone morphogenetic protein inhibitor Noggin and brain-specific angiogenesis inhibitor (BAI1). Depletion of Myo/Nog cells in explants of human anterior lens tissue and the rabbit lens during cataract surgery prevented the emergence of myofibroblasts, and in the rabbit, reduced PCO and anterior capsule opacification to below clinically significant levels. A requirement for MyoD in the differentiation of Myo/Nog cells to myofibroblasts was explored in explant cultures of human anterior lens tissue removed during cataract surgery.MethodsHuman anterior lens tissue was removed by femtosecond laser capsulotomy or curvilinear capsulorhexis during cataract surgery. Tissue was incubated in serum free DMEM/F12 medium for five days with MyoD siRNA, non-targeting siRNA or siRNA delivery buffer. In situ hybridization was carried out with fluorescent probes for human MyoD and Noggin mRNAs. MyoD, Myf5, Myogenin, alpha smooth muscle actin (α-SMA), striated muscle myosin heavy chain and Ki67 proteins were localized by immunofluorescence localization. Cell free areas of the capsule were identified by differential interference and fluorescence microscopy.ResultsApproximately seven percent of the cells in control cultures co-expressed MyoD and Noggin mRNAs. The number of MyoD mRNA-positive (+) cells was reduced by 90% after treatment with MyoD siRNA. The Noggin mRNA+ population was significantly increased with MyoD knockdown. Nearly all cells with BAI1 contained MyoD protein and all had Noggin protein. The MyoD family members Myf5 and Myogenin were also synthesized in Myo/Nog cells. More BAI1+ cells contained Myf5 than Myogenin. The majority of cells with BAI1 synthesized α-SMA and striated muscle myosin. Incubation with MyoD siRNA nearly eliminated Myogenin and striated muscle myosin, and significantly reduced the number of BAI1+ cells with Myf5. Expression of α-SMA was unaffected by MyoD knockdown. The numbers of BAI1+ and BAI1-negative (-) lens epithelial cells (LECs) increased in response to treatment with MyoD siRNA. Noggin and muscle proteins were not detected in LECs in control explants or after MyoD knockdown. Wounds, defined as areas of the capsule denuded of cells, were surrounded by Myo/Nog cells containing muscle proteins in control cultures. Wrinkles in the capsule were visible within most wounds. BAI1+/α-SMA+ cells continued to form a rim around wounds, but wrinkles were reduced by approximately 75% after MyoD knockdown.DiscussionThese results indicate that MyoD lies upstream of Myogenin, impacts Myf5 expression and is required for striated muscle myosin synthesis in Myo/Nog cells of the lens. Contractions that deform the anterior capsule are dependent on striated muscle myosin but not α-SMA. Overall, this study demonstrates that MyoD drives Myo/Nog cell differentiation to contractile myofibroblasts in primary cultures of human anterior lens tissue. While this study defines an obligatory mechanism for Myo/Nog cell differentiation, the resulting increase in the progenitor population indicates that temporary knockdown of MyoD is not a therapeutic option for preventing of PCO.